2013
DOI: 10.4236/ojmp.2013.24b003
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability, Convergent Validity and Practice Effects of the RBANS in a Memory Clinic Setting: A Pilot Study

Abstract: This pilot study examined the psychometric properties and clinical utility of a brief neuropsychological instrument (Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). The test-retest reliability, practice effects and convergent validity of RBANS were examined in participants without objective cognitive impairment. The tests were administered at two time points at approximately a two weeks' interval, with 30 cognitively intact participants with a mean age of 63.3 ± 5.8 years. Adequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…This result corroborates previous research that identified no significant increases in performance on the RBANS over short retest intervals (Dong et al, 2013) and a one year retest interval (Duff et al, 2005). Additionally, increased performance was not expected on the RBANS in the current study due to the inclusion of alternate forms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result corroborates previous research that identified no significant increases in performance on the RBANS over short retest intervals (Dong et al, 2013) and a one year retest interval (Duff et al, 2005). Additionally, increased performance was not expected on the RBANS in the current study due to the inclusion of alternate forms.…”
Section: Discussionsupporting
confidence: 92%
“…These practice effects tend to occur between the first and second testing sessions and are likely due to the small number of items on a screening measure (Falleti, Maruff, Collie, & Darby, 2006). Similar practice effects have been observed in two subtests of a more comprehensive screening measure, the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS; Randolph, 1998) over a test-retest interval of two weeks (Dong, Thompson, Tan, Lim, Pang & Chen, 2013) although the change in total RBANS score was not significant. Collectively, these studies indicate that repeated exposure to brief screening measures can result in reduced sensitivity to detect cognitive changes, particularly from the first to second test exposure.…”
mentioning
confidence: 57%
“…All outcomes were measured at baseline and post-intervention; only the RBANS and the QoL-AD were measured at the 6-week follow-up (see Tables 2-4). Test--retest reliability for the RBANS was reported at 0.80 (Dong et al 2013) and for the QoL-AD was reported at 0.76 for patients and 0.92 for caregivers (Ready & Ott, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the RBANS supplemented with CTT and mBNT has also shown convergent validity with formal neuropsychological evaluation in our previous study. 20 It could thus well be suited to routine neuropsychological diagnostic workup in a busy one-stop memory clinic, reducing the administration time to an average of 35 minutes.…”
Section: Discussionmentioning
confidence: 99%